Financial Literacy and Risk Perception to Maximize Crypto Asset Investment Decisions - Sumitra, I Made; Suidarma, I Made; Masno, Masno; Darsono, Tri; Pratama, I Gede Indra (KnE Social Sciences, 2024)
This study aims to improve investment decisions in crypto assets by optimizing the integration of financial literacy and risk perception through behavioral finance, emphasizing an in-depth understanding of the psychological and behavioral factors that influence financial decision-making. This study used a quantitative approach with primary data sourced from online questionnaires distributed via the Google Forms platform. The Slovin technique was used for sampling, resulting in a sample of 300 respondents. The analysis technique used by SEM-PLS is the Structural Equation Model Partial Least Square with the help of the SmartPLS program. The research was conducted at PT Indodax Nasional Indonesia or “INDODAX – Indonesia Bitcoin & Crypto Exchange”. The results find that the integration of financial literacy, understanding of risk through behavioral finance, and the use of technology can significantly improve investment decisions in crypto assets. This research provides in-depth insights into the relationship between financial literacy, risk perception, and investment decisionmaking in crypto assets. The theoretical implications of the study confirm that financial literacy, understanding of risk, and related education contribute to improving optimal investment decisions in crypto assets as well as shaping financial behavior. The practical implication is the need for financial organizations and educational institutions to focus on financial literacy education and risk perception training to support optimal investment decision-making in crypto assets. Keywords: financial literacy-1, risk perception-2, behavioral finance-3